Investigating the Main Factors Affecting Doing More Business with Existing Customers in Light of Customer Experience: An Empirical Study in the Malls - Al Kurdi, Barween; Nawaiseh, Aram; Alshurideh, Muhammad; Al-Ahmed, Hind; Al-Sulaiti, Khalid; Allozi, Yaser; Alzoubi, Haitham M.; Ahmed, Gouher; Alshaketheep, Khaled (International Review of Management and Marketing, 2024)
The study analyzed the relationship between four independent latent factors (emotion, communication, attitude and satisfaction) in the dependent factor (rebuying) in the presence of a moderating variable (consumers’ experience) by using a structural equation model based on the partial least squares (PLS) method. The study has applied to retail trade customers in malls. The study collected the needed data through a survey designed for this purpose. The study collected data from 300 mall shoppers. The study employs SmartPLS to analyze the data collected. The study has found that each of the independent factors significantly and positively affects the rebuying decision (a positive relationship), with the exception of the emotions factor, which had a negative impact on the rebuying decision. Also, the modified variable had a positive role in the relationship between the independent factors and the dependent factor, with the exception of the emotions factor. The effect of the modified variable caused a decline in the intensity of the relationship between these two factors.